2017
DOI: 10.1038/s41598-017-03372-x
|View full text |Cite
|
Sign up to set email alerts
|

Yield-phenology relations and water use efficiency of maize (Zea mays L.) in ridge-furrow mulching system in semiarid east African Plateau

Abstract: Yield-phenology relation is a critical issue affecting rainfed maize field productivity in semiarid east African Plateau (EAP). We first introduced Chinese ridge-furrow mulching (RFM) system to EAP, using three maize cultivars with early-, mid- and late-maturing traits as test materials. A two-year field experiment was conducted in a semiarid farm of Kenya from 2012 to 2013. Three treatments were designed: alternative ridge and furrow with transparent plastic mulching (FT), with black plastic mulching (FB) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 42 publications
1
10
0
Order By: Relevance
“…In each of the seven years of the experiment, it was proved that full plastic film mulching could promote maize grain yield, and this is consistent with previous studies in the Loess Plateau region [7,[32][33][34]. The availability of water is the key to successful dryland agriculture, and a high level of WUE is particularly important [14,35,36]; the high levels of WUE seen in the present study confirmed these findings. Nitrogen fertilization was another important factor that can affect crop production.…”
Section: Effect Of Long-term Plastic Film Mulching On Maize Yieldsupporting
confidence: 92%
“…In each of the seven years of the experiment, it was proved that full plastic film mulching could promote maize grain yield, and this is consistent with previous studies in the Loess Plateau region [7,[32][33][34]. The availability of water is the key to successful dryland agriculture, and a high level of WUE is particularly important [14,35,36]; the high levels of WUE seen in the present study confirmed these findings. Nitrogen fertilization was another important factor that can affect crop production.…”
Section: Effect Of Long-term Plastic Film Mulching On Maize Yieldsupporting
confidence: 92%
“…The shape of alternating ridges and furrows can be modified to increase the efficiency of rainfall collection. The ridges reduce rainwater run-off, and the furrows aid in water conservation 18 . Rainwater channeled to the furrows penetrates deeper into the soil profile, increases SWS, and is readily available to the plants.…”
Section: Discussionmentioning
confidence: 99%
“…Mulching technologies are common and effective practices to improve crop production worldwide, particularly in dryland areas ( Mo et al, 2017 ). Numerous studies have reported that mulching can increase soil water availability in dryland areas, mainly because of its ability to reduce soil evaporation by preventing capillarity ( Liu et al, 2017 ; Zhang P. et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%